Religious Cultural Strategy in Forming Character of Akhlakul Karimah in Students - Misriyani, Dwi; Alhamid, Idrus; Iribaram, Suparto (Jurusan Tarbiyah,IAIN PALANGKARAYA, 2025)
Religious culture as a strategy is an important step in shaping the character of students towards a more religious